Use of the light board tool as a didactic strategy during COVID-19 pandemic - Fallas Ramírez, José Manuel (2022)
After the declaration of the COVID-19 pandemic in 2020, the conventional way of teaching and learning had to move towards virtualization. The light board tool is a technology that allows conventional lessons on a blackboard to be adapted to a virtual context without losing the essence of the classroom. The objective of this work was to know the opinion of pharmacy students from the Universidad de Costa Rica about the light board employment as a didactic strategy for mathematical topics study in the context of virtualization of education due to the COVID-19 pandemic. Therefore, 19 videos were developed on the light board to explain various mathematical topics related to the Pharmaceutical Physicochemistry II and Biopharmacy and Pharmacokinetics courses of the Faculty of Pharmacy in 2020 and 2021. After its implementation, 80 students were surveyed to find their opinion about their experience related to teaching and learning processes. The data were tabulated, and the main results were graphed. All students accepted the strategy as a compliment in their study and considered it useful in their learning process. Also, more than 91 % indicated that it was helpful in the order, understanding, explanation, study, and learning of the topics with a mathematical nature. In conclusion, the light board was a good technique for developing mathematical topics, and students recommend utilizing this tool in other similar career courses.